Pendeteksi Golongan Darah Otomatis Berbasis Mikrokontroller - Fahmi Rizal Julianto; Risfendra Risfendra (Universitas Negeri Padang, 2020)
Writing this paper aims to explain the use of automatic blood type detection devices in the world of health. As for the back ground of this writing, manual testing is sometimes neffective because this method can only be done by people who are experts in this field. In the medical world blood groups are dvidedinto four, namely A, B, O, AB. This fnal project will be made using several electronic devices such as LDR, LED, LCD, speaker, and thermal print sensors. This tool uses an ATMega 32 microcontroller as a central controller and also functions to process data for determining the type of blood group. This tool uses blood objects as input data. This process of determining blood group A, B, AB, O by giving antisera A and B antisera to blood samples. Then the reading results will be displayed via LCD and speakers and print outs using thermal print. After testing, itcan be concluded that the tool can work well in detecting blood types with an accuracy of close to 100% so that it is feasible to use.